2008
DOI: 10.1002/app.27979
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of tung oil‐based composites using spent germ as a natural filler

Abstract: Novel biocomposites have been prepared by the free radical polymerization of a tung oil-based resin using spent germ, the coproduct of wet mill ethanol production, as a filler. The effect of filler particle size, amount of filler, amount of crosslinker, and molding pressure on the resulting composites has been investigated. When compared to the pure resin, an increase in storage modulus is observed when filler is added to the matrix. The thermal stabilities of the resulting composites lie between the stabiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 40 publications
4
38
0
Order By: Relevance
“…Recently, there are many research activities focusing on using vegetable oil as partial replacement of petroleum components in plastic. Vegetable oils such as soybean oil [4][5][6], linseed oil [7][8][9], corn oil [10], http and tung oil [11][12][13] contain unsaturation sites (carbon-carbon double bonds) and have been copolymerized with petroleum-based chemicals, such as styrene (ST), divinylbenzene (DVB), dicyclopentadiene (DCPD), and acrylonitrile using cationic, free radical or thermal polymerization. The properties of the resulting thermosetting polymers range from rigid plastics to soft and flexible rubbers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there are many research activities focusing on using vegetable oil as partial replacement of petroleum components in plastic. Vegetable oils such as soybean oil [4][5][6], linseed oil [7][8][9], corn oil [10], http and tung oil [11][12][13] contain unsaturation sites (carbon-carbon double bonds) and have been copolymerized with petroleum-based chemicals, such as styrene (ST), divinylbenzene (DVB), dicyclopentadiene (DCPD), and acrylonitrile using cationic, free radical or thermal polymerization. The properties of the resulting thermosetting polymers range from rigid plastics to soft and flexible rubbers.…”
Section: Introductionmentioning
confidence: 99%
“…With over 80% of its fatty acid chains bearing a conjugated triene, tung oil can react with vinyl co-monomers via cationic, thermal, or free radical polymerizations without the need of any structural modification of the triglyceride [9][10][11]. The resulting materials from the polymerization of tung oil consist of highly crosslinked thermosets.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the carbon-carbon double bonds in tung oil can readily react with vinyl co-monomers, such as DVB, ST, and dicyclopentadiene, via cationic, thermal, or free radical polymerizations, without the need for structural modifications. It has been shown that these reactions result in highly crosslinked polymer networks [12][13][14][15]. Likewise, tung oil has been used as a key component in cationic bio-based thermosets by crosslinking it with limonene and myrcene [16].…”
Section: Introductionmentioning
confidence: 99%